Immunoexpression of Ki-67 in pulmonary hypoplasia - Dzieniecka, Monika; Krystosiak, Karolina; Kulig, Andrzej (Polish journal of pathology, 2013)
Adequate pulmonary development at birth is the major determinant of postnatal outcome in the perinatal period. Lung hypoplasia is a poorly defined condition. The aim of this study was to investigate expression of Ki-67 in human fetuses with pulmonary hypoplasia compared to fetuses without pulmonary pathology and malformations of other organs used as controls. The analysis comprised 149 formalin-fixed and paraffin-embedded tissue sections from the files of the Clinical Pathology Department of the Research Institute of Polish Mother's Memorial Hospital in Lodz. Tissue sections obtained from lungs during autopsies were divided into two groups. In our studies immunohistochemistry was performed using antibody against Ki-67 as a cell proliferation marker for evaluation of growth fraction in the fetal and neonatal human lungs. The results presented in our study showed higher expression of growth fraction in the control group as compared to study subjects in all stages of lung development. Values of Ki-67 positive cells in the saccular stage of lung development were lower than in the canalicular and alveolar phase in both study and control groups. In conclusion, our results indicate their usefulness to understand better etiology of pulmonary hypoplasia and may be helpful in identifying the most appropriate moment for prenatal interventions.